OPTIMASI MODEL MATEMATIKA KEUANGAN PADA ASSET BEBAS RESIKO - Sugiyarto, Sugiyarto (Jurnal Ilmiah AdMathEdu, 2012)
This paper discuss about optimization theory and its application in finance model. The capital and the growth rate of a company are depend on amount of debt , share and dividends that are not distributed to the shareholders. Using Hamiltonian function, a companys growth movement can be analyzed and the right time and amount of dividend that will be distributed can be determined. The assumption that used in this paper is generally ,the value of growth rate is smaller than banking interest rate.   Key words: control theory, Hamiltonian function, dividend